A comparative study of heterostructured CuO/CuWO4 nanowires and thin films - Polyakov, Boris; Kuzmin, Alexei; Vlassov, Sergei; Butanovs, Edgars; Zideluns, Janis; Butikova, Jelena; Kalendarev, Robert; Zubkins, Martins (Elsevier B.V., 2017)
A comparative study of heterostructured CuO/CuWO4 core/shell nanowires and double-layer thin films was performed through X-ray diffraction, confocal micro-Raman spectroscopy and electron (SEM and TEM) microscopies. The heterostructures were produced using a two-step process, starting from a deposition of amorphous WO3 layer on top of CuO nanowires and thin films by reactive DC magnetron sputtering and followed by annealing at 650 °C in air. The second step induced a solid-state reaction between CuO and WO3 oxides through a thermal diffusion process, revealed by SEM-EDX analysis. Morphology evolution of core/shell nanowires and double-layer thin films upon heating was studied by electron (SEM and TEM) microscopies. A formation of CuWO4 phase was confirmed by X-ray diffraction and confocal micro-Raman spectroscopy.
Authors are grateful to Reinis Ignatans for XRD measurements.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; A1. Characterization; A1. Crystal morphology; A1. Nanostructures; B1. Oxides; B1. Tungstates